2014
DOI: 10.2478/jppr-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic resistance and defense-related enzymes in tomato plants using Pseudomonas fluorescens CHAO and salicylic acid against root-knot nematode Meloidogyne javanica

Abstract: Root-knot nematodes (Meloidogyne spp.) are the most economically important group of plant parasitic nematodes on many crops worldwide. Resistance-based management is considered as one of the most sound and effective strategies against these pathogens. Plant-mediated systemic resistance against the M. javanica in tomato cv. CALJN3 was triggered using salicylic acid (SA) andPseudomonas fluorescens CHAO as elicitors. The effect of each elicitor was assayed by (1) the calculation of nematode indices including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…In this study, the effects of FOL , plant hormones and PGP strains to induce CAT activity were the same. Induction of systemic resistance through defense-related enzymes POX and CAT in tomato plants treated with salicylic acid or Pseudomonas fluorescens was reported by Nikoo et al (2014). They showed that pathogen inoculation of plants treated with bacterial or hormonal elicitors increased both POX and CAT activity in higher levels compared to non-inoculated treated plants or plants only inoculated with pathogen.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the effects of FOL , plant hormones and PGP strains to induce CAT activity were the same. Induction of systemic resistance through defense-related enzymes POX and CAT in tomato plants treated with salicylic acid or Pseudomonas fluorescens was reported by Nikoo et al (2014). They showed that pathogen inoculation of plants treated with bacterial or hormonal elicitors increased both POX and CAT activity in higher levels compared to non-inoculated treated plants or plants only inoculated with pathogen.…”
Section: Discussionmentioning
confidence: 83%
“…Plant growth-promoting rhizobacteria (PGPR) has symbiont as well as non-symbiont relation with that of plant, it is a proper systematic way where the residing microflora of rhizosphere colonize it and in return promote plant growth (Benaissa. Studies were made to understand the mechanisms related to the inoculation of Pseudomonas fluorescens and salicylic acid which reduces the nematode population and also generates defence related enzymes in tomato infested with M. incognita (Sarafraz et al, 2014).…”
Section: Plant Growth Promoting Rhizobacteriamentioning
confidence: 99%
“…Plant phyto-hormones such as salicylic acid, ethylene, jasmonic and abscisic acids play an important role in signaling various pathways (Wang et al, 2007;Nikoo et al, 2014). Various roles included are regulation of processes of germination, photosynthesis, respiration, flower formation and also in post-harvest processes such as ethylene biosynthesis, fruit ripening and firmness (Thakur and Sohal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, free radicals generated by salicylic acid applied exogenously causes oxidative damage to proteins of the pathogen thus destroying the invading pathogen directly (Czajkowski et al, 2015;Nayem et al, 2017). Moreover, oxidative burst following salicylic acid application results in hydrogen peroxide being released which causes cross-linkage between cell wall components of the plant and hydroxyproline-rich glycoproteins thus making the plant cell wall tougher for digestion by pathogens (Zhang et al, 2011;Nikoo et al, 2014). Hydrogen peroxide can also cause biological damage of membranes by reacting with polyunsaturated lipids present in the cell membrane resulting in lipid peroxides being formed (Mandal et al, 2009;Zhang et al, 2011;Awan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%